Neuropeptide Mimetics and Antagonists in the Treatment of Inflammatory Disease: Focus on VIP and PACAP - Abad, Catalina; Gomariz, Rosa P.; Waschek, James A. (Current Topics in Medicinal Chemistry, 2006)
Corticosteroids are the mainstay treatment for most severe inflammatory disorders. Due to the considerable toxicity associated with their long-term use, there is a great need for alternative treatments. Recently, two closely related neuropeptides with potent neuromodulatory activities, vasoactive intestinal peptide (VIP) and pituitary adenylyl cyclase activating peptide (PACAP) have emerged as candidate molecules for the treatment of such pathologies. These peptides act primarily on three high affinity receptor subtypes expressed on multiple immune cell types, and orchestrate a cytokine response that is primarily anti-inflammatory. In this regard, systemic treatment with these peptides has been shown to greatly reduce the clinical symptoms and alter the pathogenic and cytokine profiles in animal models of rheumatoid arthritis, Crohn's disease, septic shock, and multiple sclerosis. Likewise, VIP and PACAP receptor knockout and overexpressing mice show altered immune responses in different models. We review here data demonstrating the potential effectiveness of these peptides in immune disorders, discuss receptor pharmacology and signaling pathways, describe the development of receptor specific agonists and antagonists, and discuss pharmaceutical considerations relevant to the specific delivery of analogs to the appropriate targets.
Keywords: myelinization